Profile pedagogy and modern education - Nadezhda V. Shestak; Valeriy P. Shestak (Moscow Polytechnic University, 2022)
So far as pedagogy is an applied science, profile pedagogy is a «doubled» applied science. Its function is to solve some special tasks, which appear during the organization of education or training in the chosen branch of professional activity. First of all, this relates to the realization of competence approach. Characteristics and problems of medical pedagogy are examined in this article by analogy with engineering pedagogy.